DETERMINANTS OF MANUFACTURING COMPANY STOCK PRICES - Zulher Zulher; Cicih Ratnasih (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of this study was to determine the effect of Return on Investment, Earning per Share and Dividend Per Share on the Stock Price of a manufacturing company that has several factors. Factors that influence stock price fluctuations are internal and external factors. This study uses secondary data and the population of this study are real estate and property companies that are still listed and go public on the Indonesia Stock Exchange in the 2012-2017 period. The research method and sample technique used was purposive sampling and based on several criteria selected 11 companies to be analyzed. The results of this study are the variable Return On Investment, Erning Per Share and Dividend Per Share have a positive and significant effect on stock prices. Determination Coefficient (R2) in this study has a value of 75.22% with the ability of the independent variable being able to explain the results of the stock price, while the remaining 24.78% is explained by other variables not examined. In addition, partial Return On Investment is 0.325154 <1.684 with a probability of 0.7468> 0.05. So Return on Investment has no effect on stock prices. From the results of the F test, the results show that ROI, EPS and DPS simultaneously have a significant effect on rising stock prices. Keywords: return on investment, earnings per share, dividend per share, share price of manufactured companies, Indonesia Stock Exchange.